PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 164 PEKANBARU - Nofrianti, Rati; Noviana, Eddy; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The main problem of this research is the low of learning outcomes (achievements) of fourth grade students of SD Negeri 164 Pekanbaru in social studies subjects (IPS). The purpose of this research was to improve the learning outcomes (achievements) of students in the learning of IPS by using talking stick cooperative learning model. The type of this research is classroom action research (CAR) with two cycles and through four stages that planning, implementation, observation and reflection. The analysis of the data is done by qualitative and quantitative methods. The results of this research showed that the application of the talking stick cooperative learning model has been able to improve IPS learning outcomes (achievements) of fourth grade students of SD Negeri 164 Pekanbaru. It can be seen from the data of student learning outcomes. Students average value before the classroom action were 63.97 and increased became 73.33 in cycle I. Then, its increased again became 82.17 in cycle II. The increasing percentage from the cycle I to the cycle II is 28.45%. The percentage of classical success before the classroom action was 35.89%. After that, Its increased became 58.97% in cycle I and increased again became 82.05% in cycle II.Keywords: Cooperative Learning Model, Talking Stick, IPS Learning Outcomes